Tracing the evolutionary and genetic footprints of atmospheric tillandsioids transition from land to air - Xiaolong Lyu; Ping Li; Liang Jin; Feng Yang; Boas Pucker; Chenhao Wang; Linye Liu; Meng Zhao; Lu Shi; Yutong Zhang; Qinrong Yang; Kuangtian Xu; et al. (Nature Communications)
Abstract Plant evolution is driven by key innovations of functional traits that enables their survivals in diverse ecological environments. However, plant adaptive evolution from land to atmospheric niches remains poorly understood. In this study, we use the epiphytic Tillandsioideae subfamily of Bromeliaceae as model plants to explore their origin, evolution and diversification. We provide a comprehensive phylogenetic tree based on nuclear transcriptomic sequences, indicating that core tillandsioids originated approximately 11.3 million years ago in the Andes. The geological uplift of the Andes drives the divergence of tillandsioids into tank-forming and atmospheric types. Our genomic and transcriptomic analyses reveal gene variations and losses associated with adaptive traits such as impounding tanks and absorptive trichomes. Furthermore, we uncover specific nitrogen-fixing bacterial communities in the phyllosphere of tillandsioids as potential source of nitrogen acquisition. Collectively, our study provides integrative multi-omics insights into the adaptive evolution of tillandsioids in response to elevated aerial habitats.